2019
DOI: 10.3928/02793695-20180924-03
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Versus Health Promotion Group Therapy After Traumatic Brain Injury

Abstract: The current pre- and posttest intervention study is designed for individuals with chronic symptoms and stress associated with mild-to-moderate traumatic brain injury (TBI). The researchers' intent was to evaluate whether an 8-week mindfulness-based group therapy compared to health promotion active control group therapy reduces chronic stress, TBI symptoms, and depressive symptoms. Significant mean reductions in chronic stress and TBI depressive and general symptoms for individuals in the mindfulness group comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Ten studies included control groups, and six used random assignment. Three studies used active controls, which included physical exercise (McMillan et al, 2002), outdoor walks (Johansson, Bjuhr, Karlsson, et al, 2015), and a modified version of the Health Enhancement Program (Bay & Chan, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten studies included control groups, and six used random assignment. Three studies used active controls, which included physical exercise (McMillan et al, 2002), outdoor walks (Johansson, Bjuhr, Karlsson, et al, 2015), and a modified version of the Health Enhancement Program (Bay & Chan, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The number of in‐person sessions ranged from 1 to 36 ( M = 12, SD = 8.52). In addition to in‐person group sessions ( k = 19), one study had one‐on‐one sessions (Barnes et al, 2013), one utilised group phone sessions (Bay & Chan, 2019), one used audiotapes for portable instructions (Nassif, 2013), and one included an online platform for delivery of treatment (Johansson, Bjuhr, Karlsson, et al, 2015). One study's delivery was entirely one‐on‐one (Schmid et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Acquired Brain Injury (ABI) Six studies of ABI included persons with traumatic brain injury (TBI) only as well as mixed TBI/stroke groups-304 participants overall, with 143 participants in intervention conditions and 161 participants in control conditions (Table 1). Five of the six studies received quality ratings in the moderate range (i.e., PEDro score = 5/10 or higher; Bay & Chan, 2019;Bédard et al, 2003Bédard et al, , 2014Johansson et al, 2015;McMillan et al, 2002). While five of the six studies reported significant effects (all on self-report measures), only two studies also reported corresponding effect sizes (Bédard et al, 2003(Bédard et al, , 2014.…”
Section: Overall Impact Of Mbis In the Neurorehabilitation Contextmentioning
confidence: 99%
“…Mindfulness treatments have been shown to improve: fatigue in patients with cancer [43][44][45]; anxiety, depression and quality of life in patients with myalgic encephalomyelitis/chronic fatigue syndromes [46]; chronic pain, depression relapse, addiction [41]; and, symptoms of fatigue and depression in concussion [47] [39]. Mindfulness interventions have also shown to improve prolonged symptoms of concussion [47][48][49]. In the context of PASC, Mindfulness has limitations for certain physical symptoms such as shortness of breath, lung function, or exercise intolerance [50].…”
Section: Identifying Treatment Options: Overlap Of Pasc With Related ...mentioning
confidence: 99%